Representation of Discrimination in the Animated Movie "Zootopia" (2016): John Fiske's Semiotic Analysis - Alvina Putri Murdiyanti; Yeny Prastiwi (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2025)
This study explores the representation of discrimination in the animated film Zootopia through a semiotic analysis based on John Fiske's three levels of codes: reality, representation, and ideology. The research aims to identify how visual and narrative elements convey ideological messages about social inequality, prejudice, and systemic bias. At the reality level, discrimination is depicted through observable details such as clothing, physical appearance, gestures, and speech patterns. These elements highlight the unequal treatment of characters based on species, size, gender, and class—revealing how social roles are visually and culturally constructed. At the representation level, these real-world cues are translated into specific character interactions and storylines, such as Judy Hopps' struggle for acceptance as a rabbit police officer or Mayor Lionheart's domination over Assistant Mayor Bellwether. These scenes expose the mechanisms by which stereotypes and biases are perpetuated in society. At the ideological level, the film critiques hierarchical power structures and the symbolic markers that maintain social divisions—such as clothing, spatial segregation, and occupational roles. The findings reveal that Zootopia not only reflects existing societal norms but also challenges viewers to question and resist prejudice and discrimination. Through this layered analysis, the study concludes that Zootopia is a powerful medium for raising awareness about discrimination, encouraging audiences to reflect on issues of diversity, privilege, and social justice in both fictional and real-world contexts.